The role of dietary fibre in inflammatory bowel disease - Pituch-Zdanowska, Aleksandra; Banaszkiewicz, Aleksandra; Albrecht, Piotr (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
The aetiology of inflammatory bowel diseases (IBD), which are primarily Crohn’s disease and ulcerative colitis, still remains unclear, while the incidence of IBD is constantly increasing, especially in the industrialised countries. Among genetic, environmental, and immunological factors, changes in the composition of the intestinal microflora and diet are indicated as very important in initiating and sustaining inflammation in patients with IBD. Above all nutrients dietary fibre is an especially important component of diet in the context of IBD. A potentially protective effect of high-fibre diet on intestinal disorders was described as early as in 1973. Several trials performed in animal models of IBD and human studies have reported that supplementation of some types of dietary fibre can prolong remission and reduce lesions of the intestinal mucosa during the course of the disease. This paper presents the current state of knowledge on the effects of dietary fibre in IBD.